Anti-angiogenic effects of the blue-green alga Arthrospira platensis on pancreatic cancer - Marková, Ivana; Koníčková, Renata; Vaňková, Kateřina; Leníček, Martin; Kolář, Michal; Strnad, Hynek; Hradilová, Miluše; Šáchová, Jana; Rasl, Jan; Klímová, Zuzana; Vomastek, Tomáš; Němečková, Ivana; et al. (Journal of cellular and molecular medicine, 2020)
Arthrospira platensis, a blue-green alga, is a popular nutraceutical substance having potent antioxidant properties with potential anti-carcinogenic activities. The aim of our study was to assess the possible anti-angiogenic effects of A platensis in an experimental model of pancreatic cancer. The effects of an A platensis extract were investigated on human pancreatic cancer cells (PA-TU-8902) and immortalized endothelial-like cells (Ea.hy926). PA-TU-8902 pancreatic tumours xenografted to athymic mice were also examined. In vitro migration and invasiveness assays were performed on the tested cells. Multiple angiogenic factors and signalling pathways were analysed in the epithelial, endothelial and cancer cells, and tumour tissue. The A platensis extract exerted inhibitory effects on both migration and invasion of pancreatic cancer as well as endothelial-like cells. Tumours of mice treated with A platensis exhibited much lesser degrees of vascularization as measured by CD31 immunostaining (P = .004). Surprisingly, the VEGF-A mRNA and protein expressions were up-regulated in pancreatic cancer cells. A platensis inhibited ERK activation upstream of Raf and suppressed the expression of ERK-regulated proteins. Treatment of pancreatic cancer with A platensis was associated with suppressive effects on migration and invasiveness with various anti-angiogenic features, which might account for the anticancer effects of this blue-green alga.
Keywords: signální transdukce; upregulace; Signal Transduction; inhibitory angiogeneze; myši nahé; carcinogenesis; nádory slinivky břišní; Humans; Up-Regulation; angiogenesis; Antineoplastic Agents; pancreatic cancer; Mice, Nude; lidé; Antioxidants; zvířata; myši; anticancer effects; Mice; Neovascularization, Pathologic; antioxidancia; pohyb buněk; Endothelial Cells; Pancreatic Neoplasms; Angiogenesis Inhibitors; Cell Movement; nádorové buněčné linie; protinádorové látky; endoteliální buňky; Animals; Cell Line, Tumor; Arthrospira platensis; Spirulina; patologická angiogeneze